Cerita Oey Se Sebagai Refleksi Struktur Sosial Indonesia Era Kolonial - Gindho Rizano (English Study Program, Faculty of Humanities, Universitas Andalas, Padang, 2021)
Chinese-Indonesian literature in Malay have been outshined by the canonized and goverment-backed Balai Pustaka. However, an analysis of a representative book using a proper theory allows us not only to take a glimpse of the social dynamics of the colonial time, but also to see its literary worth. This paper applies mainly Georg Lukacs’ idea of reflection theory to Cerita Oey Se, a novel about the rise of a Chinese merchant of Indonesian colonial time and his subsequent personal problems. The main findings are: (1) The work reflects the socio-political condition of Indonesian colonial time in its ‘totality’along with its inherent contradictions. (2) The work functions as an implicit critical discourse toward the colonial and the capitalist social structure. (3) The idea that Indonesian-Chinese literary works are of little value is groundless, since this work among others, fits the criteria of good literary in its capacity to reflect the essential structure of Indonesian society of the late 1800s.